2002
DOI: 10.4049/jimmunol.168.10.4881
|View full text |Cite
|
Sign up to set email alerts
|

Death Ligand TRAIL Induces No Apoptosis but Inhibits Activation of Human (Auto)antigen-Specific T Cells

Abstract: TNF-related apoptosis-inducing ligand (TRAIL), a member of the TNF superfamily, induces apoptosis in susceptible cells, which can be both malignant and nontransformed. Despite homologies among the death ligands, there are great differences between the TRAIL system on the one hand and the TNF and CD95 systems on the other hand. In particular, TRAIL-induced apoptosis differs between rodents and man. Studies on animal models of autoimmune diseases suggested an influence of TRAIL on T cell growth and effector func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 38 publications
7
89
1
2
Order By: Relevance
“…Our results demonstrating more robust proliferation of TRAIL KO CD8 ϩ T cells are supported by work in humans demonstrating that TRAIL decreases proliferation of Ag-specific T cell lines (17), particularly CD8 ϩ T cell blasts (57). Moreover, it has been shown recently that TRAIL is a key negative regulator of secondary CD8 ϩ T cell responses.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results demonstrating more robust proliferation of TRAIL KO CD8 ϩ T cells are supported by work in humans demonstrating that TRAIL decreases proliferation of Ag-specific T cell lines (17), particularly CD8 ϩ T cell blasts (57). Moreover, it has been shown recently that TRAIL is a key negative regulator of secondary CD8 ϩ T cell responses.…”
Section: Discussionsupporting
confidence: 85%
“…For example, in vitro data indicate that TRAIL can either suppress or costimulate T cell responses depending on whether it acts as a ligand or as a receptor, respectively (17)(18)(19). In vivo studies using TRAIL knockout (KO) mice or TRAIL blockade have demonstrated exacerbation of disease in murine models of collagen-induced arthritis (20), diabetes (21)(22)(23), and experimental autoimmune encephalomyelitis (24).…”
Section: T Cell Trail Promotes Murine Lupus By Sustaining Effectormentioning
confidence: 99%
“…Death receptor ligation on CD4 + or CD8 + T cell blasts induces, to different extents, cell cycle arrest in G 2 /M. A previous study described inhibition of growth in the absence of apoptosis induction by rApo2L on long-term autoreactive CD4 + T cell lines [35]. In that case, it was reported that rApo2L induced a decrease in CDK4 expression, and the authors concluded that, in consequence, rApo2L should induce cell cycle arrest at the G 1 /S transition.…”
Section: Discussionmentioning
confidence: 98%
“…In line with this notion are previous reports showing that TRAIL inhibits DNA synthesis in human autoreactive T cells and prevents progression from G1 to S phase, without inducing apoptosis. 35 Apart from these direct effects of TRAIL on autoreactive T cells, TRAIL may regulate autoimmunity also at the level of antigen-presenting cells. As mentioned above, DC may become sensitive to TRAIL-induced apoptosis under certain conditions, and thus reduced antigen presentation will result in reduced T-cell activation and downregulation of the (auto-) immune response.…”
Section: Role Of Trail In Immune Regulation Immunopathologies and Aumentioning
confidence: 99%